Pemodelan Perlapisan Bawah Permukaan Manifestasi Semburan Gas Biogenik di Kampung Holtekamp Jayapura Menggunakan Metode Elektromagnetik Pasif - Bangkit Sudrajad (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2026)
Natural gas is a natural resource abundant in Indonesia. This abundance of natural gas potential makes Indonesia one of the world's natural gas producers. Papua is one of the regions in Indonesia with large potential natural gas reserves, including in the Jayapura area. The existence of biogenic gas potential in the Jayapura City area is indicated by the biogenic gas eruption that emerged during the drilling process of a well by residents of Holtekamp Village, Muara Tami District, Jayapura City. This gas eruption incident caused unrest among residents. The gas eruption that appeared in the Holtekamp Village area is not the first in the Muara Tami District area but has also been found in West Koya. In relation to this, geophysical research was conducted using a passive electromagnetic survey method. This method is used to determine the condition of the subsurface structure locally. Based on the results of the electromagnetic modeling method, the results showed that the condition of the subsurface layer structure at the location of the natural gas well eruption manifestation is a layer of coastal sediment and swamp areas that have several layers of aquifers, aquitards, and aquicludes. The identified aquifer layers consist of an unconfined aquifer layer near the surface; A confined aquifer containing a gas trap, and a leaky aquifer that allows natural gas to migrate from deeper to shallower aquifers. The leaky aquifer is supported by the identification of an aquitard capable of transmitting fluid migration. In the gas trap area, an aquiclude layer, a wet clay layer (claycap), was identified at a depth of 27.5-28 meters. This claycap layer traps the pressurized gas at that location.